Comparative aspect of study of plant images in Russian and German linguistic cultures: nominations and metaphors - G. M. Bovaeva; T. V. Buraeva (Nomadic Civilization: Historical Research)
The article is devoted to studying ethnocultural specifics of images of plants in Russian and German phraseology. The aim of the study of this article is to identify the universal and individual features of phraseological phytonyms in the considered language cultures. It is shown that in Russian culture the most important flower symbols are cucumber, lemon, cone and in German “cabbage”, “tree”, “apple”, “bean”, “burdock”. All of a person’s “vegetable” units of expression are systematized into possible groups: 1) external data and a person’s physical condition; 2) intelligence, heredity, life experience; 3) Character traits and relationships between people. The dominant sphere sources of the phytonym metaphor are revealed. The classification of metaphorical models is developed. The spe- cific character of the metaphorical forms of “plant” in the Russian and German language culture is defined and the typology of the metaphors that structure the phytonym concept on different cognitive bases is given. The analysis of the metaphorical representations in linguistic-cultural terms makes it possible to define the specificity of the national character and worldview of the Russians in comparison with the Germans. Thus, the phraseological image of the German and Russian languages serves as a “mirror” of perception and representation of the worldview of each ethnic group. This explains the national-cultural specificity of the phraseologisms in the languages concerned.